A Variable-Speed Approach for Preventing Cam-Follower Separation - Hong-Sen YAN; Wu-Jung TSAI (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2008)
The follower separation is a major impediment to the operating speed increase of force-closed cam mechanisms. This problem traditionally is solved by increasing the spring preload or spring rate to enlarge the return force. An alternative approach with variable cam speed is proposed to prevent follower separation and thereby to raise the average operating speed. By properly designing the cam speed to change the follower motion, the critical motion characteristics leading to follower separation can be avoided. The cam speed trajectory is expressed using the Bezier function. A mathematical model is developed for analyzing the cycle time and the critical times of follower separation. Then a design model for optimizing the critical average cam speed without follower separation is developed to specify the design parameters of this trajectory. Two design examples with different cam motion programs are given for demonstrating the feasibility of this approach.